2011
DOI: 10.1038/onc.2011.130
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic mass spectrometry profiling links Src family kinases to escape from HER2 tyrosine kinase inhibition

Abstract: Despite the initial effectiveness of the tyrosine kinase inhibitor lapatinib against HER2 gene-amplified breast cancers, most patients eventually relapse after treatment, implying that tumors acquire mechanisms of drug resistance. To discover these mechanisms, we generated six lapatinib-resistant HER2-overexpressing human breast cancer cell lines. In cells that grew in the presence of lapatinib, HER2 autophosphorylation was undetectable whereas active PI3K-Akt and MAPK were maintained. To identify networks mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
123
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 51 publications
13
123
0
Order By: Relevance
“…We previously showed that LR cells exhibit continued activation of PI3K signaling despite inhibition of the HER2 tyrosine kinase [25]. To identify mechanisms associated with maintenance of PI3K signaling in these drugresistant cells, we profiled them using the SNaPshot assay [27- Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that LR cells exhibit continued activation of PI3K signaling despite inhibition of the HER2 tyrosine kinase [25]. To identify mechanisms associated with maintenance of PI3K signaling in these drugresistant cells, we profiled them using the SNaPshot assay [27- Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…SUM190 cells were purchased from Asterand (Detroit, MI, USA). Lapatinibresistant (LR) cell lines were generated as described previously [25] and cultured in the presence of 1 to 2 μM lapatinib. Lapatinib ditosylate and BIBW2992 were obtained from LC Laboratories (Woburn, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…2). In particular, SFKs have been shown to be hyperactivated in breast cancer lines whose resistance is associated with the increased expression of certain RTKs, including ErbB2 itself, EGFR, and IGF1R (Rexer et al 2011;Zhang et al 2011), as well as cells that mediate an alternative survival pathway through b1 integrin ). Moreover, SFKs may help drive resistance in cells that overexpress RTKs by initiating a positive feedback loop.…”
Section: Src Enters the Fray As An Important Signaling Nodementioning
confidence: 99%
“…However, as observed with CA125 earlier, if high-molecular weight proteins are examined, the presence of PTMs may obscure the data; analyses must therefore be tailored to specific events, such as phosphorylation or glycosylation. It has been demonstrated that resistance to the TKI lapatinib in breast cancer cell lines is linked to increased phosphorylation of Src family kinases (Rexer et al 2011). Further, by treating these cells with Src inhibitors, the sensitivity to lapatinib is restored.…”
Section: Interaction Proteomicsmentioning
confidence: 99%